El acto de borrar - Bonilla Rius, Ana (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2006)
The act of erasing reveals issues of the self, of the self esteem and of the relation with the world. This act implies a number of psychological and behavioural instances towards us and towards our relationship with the sight of the other. It is important to refl ect on this essential issue within an Art Therapy session.